Pengaruh penanaman modal asing dan penanaman modal dalam negeri terhadap pertumbuhan ekonomi dan pengangguran di Indonesia - Suprianto Suprianto; Syaparuddin Syaparuddin; Siti Hodijah (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
This study aims to analyze the influence of Foreign Investment (PMA) and Domestic Investment (PMDN) on economic growth and unemployment in Indonesia. The data used is Indonesia's secondary data for the period 2000 - 2014 which includes PMDN, PMA, unemployment, and economic growth. Data is sourced from the Central Bureau of Statistics, Bank Indonesia and the Asian Development Bank. The main analysis tool is multiple linear regression. The results of the study found that: 1) simultaneously and partially PMA and PMDN had a significant effect on Indonesia's economic growth; 2) simultaneously PMA and PMDN have a significant effect on unemployment in Indonesia. However, only partially PMDN has a significant effect.